PENGARUH PEMASARAN VIRAL, SELEBRITI ENDORSER DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN LAZADA (Studi Kasus Pada Mahasiswa Universitas Islam Malang Fakultas Ekonomi Dan Bisnis) - Andre A khriza Pradana; N. Rachma; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This study aims to examine and analyze the effect of viral marketing, celebrity endorsers, and brand awareness simultaneously and partially on purchasing decisions. The variables used in this research are Viral Marketing (X1), Endorse Celebrity (X2), Brand Awareness (X3) on Purchasing Decisions (Y). Viral Marketing (X1) on Referral Decisions, Celebrity Endorsers (X2) on Referral Decisions (Y), Brand Awareness (X3) on Referral Decisions (Y). The population in this study were students of the Islamic University of Malang, Faculty of Economics and Business, whose exact number was not known, so the sample used Malhotra, so the sample in this study was taken by purposive sampling method, namely the sampling technique based on certain considerations, which are considered suitable with the characteristics of the sample. which is determined so that will be the sample in this study is 100 samples (20 item questions x 5) data collection methods data collection is done by questionnaire. By preparing instruments in the form of written questions, in order to make the research easier, closed questions were used in this study, namely each question that had been provided with an answer that the respondent could choose from. The data analysis technique used in this study is multiple linear regression, the results of the study state that partially viral marketing has an effect on purchasing decisions. Celebrity Endorser influences Purchasing Decisions. Brand Awareness affects Purchasing Decisions. And simultaneously Viral Marketing, Celebrity Endorsers, and Brand Awareness influence Purchasing Decisions. Keywords: Viral Marketing, Celebrity Endorsers, Brand Awareness and Purchasing Decisions